A study of the compression stability of a coupler under initial asymmetric conditions. (July 2022) - Zou, Ruiming; Luo, Shihui; Ma, Weihua
In practice, due to the influence of assembly deviation, clearance, vibration and other objective factors, the coupler will inevitably work under asymmetrical conditions in the buffing state. However, the existing theoretical studies on the compression stability of couplers did not pay enough attention to this condition, and most of the studies are based on the premise of ideal symmetry conditions. In this paper, the initial lateral deviation between the ends of a coupling coupler is taken as a typical asymmetrical condition, and the influence of the initial asymmetrical condition on the compression stability of the coupler is analysed by theoretical analysis and dynamic simulation. The results show that with the increase of the initial lateral deviation, the rotation angle of the coupler will also increase when it reaches the self-stabilizing equilibrium point. Therefore, the initial asymmetry will reduce the stability margin of the coupler, and then weaken the self-stabilizing ability and compression stability of the coupler. Improving the symmetry of the coupler is also one of the effective methods to guarantee the compression stability of the coupler and the running safety of the locomotive. When the static friction coefficient of the coupler tail can reach 0.3, the initial lateral deviation of the coupler should be limited to less than 7 mm, and the smaller the static friction coefficient, the higher the requirements for the initial lateral deviation.